AI-Driven Precison Agriculture and Crop Health Prediction System (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Precision agriculture technologies have historically relied on expensive physical sensor networks and computationally prohibitive deep-learning architectures, creating severe financial and technical barriers for marginal farmers. To address this disparity, this paper presents the Smart Agro Advisor, a highly optimized, zero-hardware web ecosystem designed to democratize agronomic intelligence. Utilizing an asynchronous Python FastAPI architecture, the system integrates lightweight Scikit-Learn machine learning algorithms to perform real-time crop suitability and precise fertilizer dosage predictions. To bypass the extreme GPU requirements of traditional Convolutional Neural Networks (CNNs), this research introduces a novel, deterministic color-space (HSV) heuristic pipeline capable of instantaneous plant pathogen classification and soil type validation directly in the browser. Furthermore, the system entirely replaces physical IoT hardware by programmatically intercepting real-time telemetry from external cloud APIs, including OpenMeteo for hourly weather forecasting and Live Market APIs for economic intelligence. To ensure practical usability for demographics with limited digital literacy, the platform is encapsulated in a responsive Glassmorphic user interface fortified with Web Speech API integration, enabling full Voice-to-Text accessibility. Evaluation of the deployed architecture demonstrates robust algorithmic accuracy exceeding 92% across all models, alongside sub-second end-to-end inference latency, proving that accessible, API-driven software frameworks can successfully replace prohibitive hardware infrastructure in rural agriculture.